Perbandingan Rasio Profitabilitas Perusahaan Sektor Pertambangan yang Terdaftar di BEI Sebelum dan Selama Pandemi Covid-19 - Fadhil Muhaimin Nadhip; Leni Nur Pratiwi; Anny Suryani (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to analyze the comparison on profitability ratio towards mining sector companies that are listed in Indonesia Stock Exchange before and during the Covid-19 pandemic for the 2019-2020 period. The research method used is financial ratio different test between before and during Covid-19 pandemic. Financial ratio that is used is profitability ratio consisting of gross profit margin, net profit margin, return on asset, and return on equity. Data analysis using IBM SPSS ver. 25. The result if this study is stated that there is a significant difference towards profitability ratio between before and during the Covid-19 pandemic.